The Effect of Nano Materials on the Rheological Properties of Asphalt Binder - Yousif, Rana A.; Abed, Haneen M. (Engineering, Technology & Applied Science Research, 2025)
This study investigates the effects of nano-silica, nano-chitosan, and nano-clay as asphalt binder modifiers, focusing on their physical and rheological properties. The nanomaterials were incorporated at concentrations of 2.5%, 5.0%, 7.5%, and 10% by weight. This research was driven by the growing adoption of nanomaterials, many of which are known for their toxicity and environmental impact. The results demonstrated a significant improvement in both physical and rheological properties, particularly in rutting resistance. Nano-silica demonstrated the greatest enhancement, leading to a reduction in permeability values, an increase in softening point, viscosity, and overall resistance to permanent deformation. Nano-chitosan exhibited a similar trend but with slightly lower performance values than nano-silica. Nano-clay provided the least improvement, though it still contributed to increased asphalt binder stiffness and reduced temperature sensitivity. Overall, the findings confirm that nano-silica, nano-chitosan, and nano-clay can improve asphalt binder properties, extending pavement lifespan and performance under increasing traffic demands. Further studies are recommended to explore the long-term aging resistance, fatigue behavior, and field applications of these nanomaterial-modified asphalt binders.